Mejoramiento del poblaciones de arroz de secano empleando selección recurrente y desarrollo de variedades - Chatel, Marc; Guimarães, Elcio Perpétuo; Ospina, Yolima; Rodríguez, Francisco; Lozano, Víctor Hugo (International Center for Tropical Agriculture, 2010)
Improving upland rice populations using recurrent selection and varietal development The new breeding methods used by the collaborative rice improvement project carried out by CIAT and the French Agricultural Research Centre for International Development (CIRAD) are described: development of populations with a broad genetic base and recurrent selection. This project aims to continue to develop improved varieties while broadening the variability of germplasm available to farmers. A recessive male-sterile gene (ms) found in a mutant of variety IR36 facilitated the development of the rice population. Site-specific composite populations were developed with the national agricultural research institutes. In the case of Colombia, several composite populations were improved using two methods of recurrent selection. Several fertile plants were selected at each breeding stage and then used as a starting point to develop segregating and fixed lines using the conventional pedigree method. Since 2002, more than 90% of the lines in the selection process have come from original and improved recurrent populations. The most advanced lines are currently being evaluated in observation nurseries and yield trials in collaboration with different project partners in South America (Argentina, Bolivia, Brazil, Colombia, and Venezuela), Central America (Nicaragua), and the Caribbean (Cuba). Several promising lines, which could become commercial varieties, have been identified.